Menopausal Issues And Complications Among Women In Budgam District Of Kashmir Region. - Irshad, Naila; Sumera (International Journal of Psychosocial Rehabilitation, 2020)
Menopause, not being an ill health, is simply the period in a woman’s life when menstruation ends. It is a regular as well as innate biological process that involves the ageing of the reproductive system. Women experience numerous symptoms and complications throughout this phase, like vascular instability, urogenital atrophy, joint pain, fornication, and psychological and sexual discomforts, and these are diverse for every woman. The main objective of this paper is to highlight the age at which menopause mostly occurs and the symptoms and complications related to menopause. Furthermore, it aims at ascertaining the opinion and remedies adopted for menopausal problems. A study on common problems during menopause was carried out on 150 women respondents. The sample was collected from the Budgam district of the Jammu and Kashmir state. A comprehensive questionnaire was drafted to obtain information regarding personal details, sexual, physiological, psychological, and general health problems. It was found that most commonly menopause occurs at the age of 50-55 years. For some, these changes initiate early, whereas others reach menopause late. A biochemical investigation (hormone balance check) could not be conducted because of the non-availability of funds. This study was intended to help the various people involved in the healthcare system to be more informed and decisive about the various decisions to be taken for improving the quality of healthcare. This would be attained by reducing the cost of health care and addressing the safety of patients and various medical errors in addition to widening access to health services.